2001
DOI: 10.1097/00006231-200110000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for detecting knee replacement infections based on extended combined99m Tc-white blood cell/bone imaging

Abstract: The purpose of this study was to evaluate whether an extension of the imaging time to 24 h post-injection improves the diagnostic accuracy of technetium-99m-hexamethylpropyleneamine oxime (99mTc-HMPAO) leucocyte imaging in detecting knee replacement infections. Thirty patients were studied, with infection confirmed in eight (27%) and excluded in 22 on the basis of clinical and microbiological findings. Leucocyte imaging was carried out at 2-4 h (routine images) and at 24 h (late images) post-injection. For com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
15
0
4
Order By: Relevance
“…Larikka et al reported improved sensitivity (83 vs 50% and 100 vs 87% for hip and knee prostheses, respectively) and specificity (100 vs 90% and 82 vs 77% for hip and knee prostheses, respectively) by comparing early (4-6 h) and late (20-24 h) 99m Tc LS [35,36]. Fernandez et al came to similar conclusions, in a study with 49 prosthetic joint implants.…”
Section: Bsmentioning
confidence: 71%
See 1 more Smart Citation
“…Larikka et al reported improved sensitivity (83 vs 50% and 100 vs 87% for hip and knee prostheses, respectively) and specificity (100 vs 90% and 82 vs 77% for hip and knee prostheses, respectively) by comparing early (4-6 h) and late (20-24 h) 99m Tc LS [35,36]. Fernandez et al came to similar conclusions, in a study with 49 prosthetic joint implants.…”
Section: Bsmentioning
confidence: 71%
“…These relatively unsatisfactory results reported for LS, performed as the only radionuclide imaging technique, have been attributed to several factors, such as (1) the presence of a chronic or low-grade infection with fastidious microorganisms and the presence of a biofilm around the infected prosthesis (decreasing its sensitivity) [35,36], (2) the possible negative influence of administered antibiotics (decreasing its sensitivity) [37], (3) the non-specific inflammation in the neighbouring soft tissues (decreasing its specificity), (4) the interfering problem of ectopic bone marrow present in the appendicular skeleton, particularly induced by prosthetic surgery (decreasing its specificity) [38][39][40][41], and last but not least (5) the inability to develop a generally accepted acquisition protocol in combination with the lack of a satisfactory analysis method for interpretation of the images [2,42,43].…”
Section: Ant Antmentioning
confidence: 99%
“…Le Tableau 2 rapporte les principales études et leurs résultats [24]. Des auteurs ont rapporté une diminution de la sensibilité en présence d'une infection chronique évoluant à bas bruit avec un biofilm protecteur des bactéries en cause [23,25], mais aussi en cas d'antibiothérapie en cours [26]. L'inflammation non spécifique des tissus adjacents peut diminuer la spécificité ainsi que la présence de moelle osseuse réactionnelle autour de biomatériaux pour laquelle certains auteurs ont proposé l'association d'une scintigraphie médul-laire aux sulfocolloïdes pour améliorer la spécificité, mais principalement avec les leucocytes marqués à l' 111 In, peu avec le 99m Tc (Fig.…”
Section: La Scintigraphie Aux Polynucléaires Marqués (Spm) Autologuesunclassified
“…Die 3-Phasen-Skelettszintigraphie mit 99m Technetium-Methyldiphosphonat besitzt eine hohe Sensitivität für entzündliche Prozesse, jedoch nur eine Spezifität von 0,05 zur Diagnostik einer periprothetischen Infektion und kann damit lediglich zur Ausschlussdiagnostik eingesetzt werden [6,11]. Die 67 Gallium-Zitrat-Szintigraphie weist ebenfalls eine zu geringe Spezifität auf und wird heute unter dieser Fragestellung nicht mehr verwendet.…”
Section: Bildgebungunclassified